Comparison of national E&T-cultures: findings of a transnational research project in UK, Germany, Italy, France and Portugal - Michael Kuhn (Adult Education Research Conference, 2000)
The paper presents the findings of a transnational project shedding some light on the role of national VET-cultures in 5 EU-member-states performing joint labour market policies. In focus group interviews with the main social actors in VET, trainees, industrialists and trainers, both intra-cultural between the groups and inter-cultural differences between the countries will be investigated.